A phase sensitive modulated thermography of debondings in the insulator of SRMs. (February 2017) - Guo, Xingwang; Zhang, Nannan
Abstract: Solid rocket motors (SRMs) have been widely applied in missiles, space rockets and shuttles. However, because of some technological and environmental reasons, debonding or poor bonding usually appears in the insulator of SRMs. To evaluate the bonding state between the insulator and the shell during manufacturing, a phase sensitive modulated thermography (MT) is proposed. In order to optimize the operating condition, the influences of the modulation frequency, insulator thickness and debonding lateral size on defect signals are studied through experimentation and 3D numerical simulation. Finite element analysis (FEA) using ANSYS software is applied to simulate the thermal process of the structures precisely. The results show that phase sensitive MT is an effective approach to detect the debondings in the adhesion interfaces. The phase difference at the modulation frequency can be expressed as a quintic polynomial of the modulation frequency in the usual operating frequency range, and the best modulation frequency and detectable frequency band can be determined by the polynomial; when the insulator thickness increases, the best modulation frequency and the maximum phase difference decrease; when the debonding lateral size increases, the maximum phase difference increases while the best modulation frequency remains unchanged. The results provide a guideline for the MT of debondings in SRMs.